(untitled) (Research, Society and Development, 2021)
This research aimed to review the literature about retrospective studies carried out within the scope of the Covid-19 pandemic, which reported on the nutritional therapy used for patients with the disease admitted to Intensive Care Units. The integrative review was carried out from searches in electronic databases about publications of original articles written in English and Portuguese, between the years 2019 to 2021. The searches were carried out in the databases: Science Direct (Elsevier virtual library), Scielo (Scientific Electronic Library Online), Pubmed / Medline (Medical Literature Analysis and Retrievel System Online) and VHL (Virtual Health Library), using the words SARS-CoV-2, Enteral Nutrition, Parenteral Nutrition and Health Unit as descriptors. Intensive Care, in English and Portuguese. After the search and selection process using the criteria cited in the methodology, 3 articles were selected. Nutritional therapy is a fundamental part of the recovery process for critical patients with Covid-19, since within the hospitalization period the malnutrition process is accelerated, due to the hypercatabolic clinical characteristic of the disease related to metabolic disorders. Some guidelines about nutritional therapy for patients with Covid-19 have already been created from statements by professionals linked to clinical nutrition societies, and the recommendations have been widely used as therapeutic principles in medical care centers for patients in this pathological state.